PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN DAN MINAT BELI PADA RANCH MARKET - Saidani, Basrah; Arifin, Samsul (Fakultas Ekonomi, Universitas Negeri Jakarta, 2012)
This study aims to describe clearly about product quality, service quality, customer Satisfaction and repurchase intention on customer at Ranch Market Pondok Indah South Jakarta . The second objective is to test the influence of product quality and service quality to customer satisfaction and repurchase intention. The third objective is to test the influence of product quality and service quality to customer satisfaction. The fourth objective is to test the influence product quality and service quality to repurchae intention. The fifth objectives is to test the influence customer satisfaction to repurchase intetsion. Population of the research is Ranch Market customer at Pondok Indah South Jakarta. Sampling totaled 160 respondents. Analysis of the research was conducted using SEM (struktural equation model) Lisrel statistical application program version 8.80 for data processing. Descriptive analysis results showed: a) Performance dimension is the most dominant dimension in product quality variable, b) Responsiveness dimension is the most dominant dimension in service quality variable, c) Attribute related to service is the most dominant dimension in customer satisfaction variable, d) Transactional is the most dominant dimension in repurchase intention variable. The results of hypothesis testing are: 1) product quality and service qualitry influence the customer satisfaction and repurchase intention, 2) product quality and service quality influence the customer satisfaction, 3) product qualityand service quality influence the repurchase intention, 4) customer satisfaction influence the repurchase intention. Keywords: Product Quality, Service Quality, Customer Satisfaction, Repurchase Intention.